Performance Comparison Between Fuzzy Logic Controller (FLC) and PID Controller for a Highly Nonlinear Two-wheels Balancing Robot - Mohd Riduwan, Ghazali; Ahmad Nor Kasruddin, Nasir; Mohd Ashraf, Ahmad; Nasrul Salim, Pakheri (2011)
Abstract—The research on two-wheels balancing robot has gained momentum due to their functionality and reliability when completing certain tasks. This paper presents investigations into the performance comparison of Fuzzy Logic Controller (FLC) and PID controller for a highly nonlinear 2– wheels balancing robot. The mathematical model of 2-wheels balancing robot that is highly nonlinear is derived. The final model suffers from mismatched condition. Two system responses namely the robot position and robot angular position are obtained. The performances of the FLC and PID controllers are examined in terms of input tracking capability. Simulation results of the responses of the nonlinear 2–wheels balancing robot are presented in time domain. A comparative assessment of both control schemes to the system performance is presented and discussed.